Contraceptive Use and Associated Factors among Women Enrolling into HIV Care in Southwestern Uganda. (3rd October 2012) - Muyindike, Winnie; Fatch, Robin; Steinfield, Rachel; Matthews, Lynn T.; Musinguzi, Nicholas; Emenyonu, Nneka I.; Martin, Jeffrey N.; Hahn, Judith A.
Abstract : Background . Preventing unintended pregnancies among women living with HIV is an important component of prevention of mother-to-child HIV transmission (PMTCT), yet few data exist on contraceptive use among women entering HIV care. Methods . This was a retrospective study of electronic medical records from the initial HIV clinic visits of 826 sexually active, nonpregnant, 18–49-year old women in southwestern Uganda in 2009. We examined whether contraceptive use was associated with HIV status disclosure to one's spouse. Results . The proportion reporting use of contraception was 27.8%. The most common method used was injectable hormones (51.7%), followed by condoms (29.6%), and oral contraceptives (8.7%). In multivariable analysis, the odds of contraceptive use were significantly higher among women reporting secondary education, higher income, three or more children, and younger age. There were no significant independent associations between contraceptive use and HIV status disclosure to spouse. Discussion . Contraceptive use among HIV-positive females enrolling into HIV care in southwestern Uganda was low. Our results suggest that increased emphasis should be given to increase the contraception uptake for all women especially those with lower education and income. HIV clinics may be prime sites for contraception education and service delivery integration.